Peran Kepemimpinan Dalam Meningkatkan Kualitas Manajemen Kurikulum - Masrany Banjarnahor (CV Putra Publisher, 2024)
This research aims to determine and explain the close relationship between leadership and management curriculum in an educational context. Leadership in curriculum management does not only include the ability to provide direction and goals, but also includes the ability to motivate, inspire and guide the team in implementing the curriculum effectively. This research also describes leadership indicators in the management curriculum, including the vision of curriculum development and objectives, curriculum organization and planning, curriculum implementation, curriculum monitoring and evaluation, as well as curriculum renewal and innovation. This research uses a library study method to examine the concept of leadership and curriculum management.